대학 작문 교육의 현실과 정체성에 관한 연구 - 선행 연구의 흐름과 실태 분석을 통한 표준 교육과정을 제안하며 - 허재영 (교양교육연구, 6(1), 2012)
이 글은 대학 작문 교육의 현실을 진단하고, 대학 작문 교육의 정체성을 찾기 위한 목적에서 출발한 글이다. 대학 작문 교육의 위상 정립과 정체성 확립을 위해서는 근본적으로 고찰되어야 할 문제가 많다. 거시적 안목에서 대학 교육과정 설계의 원리, 전공 교육과정과 교양 교육과정의 상관성, 교양 교육과정 내에서 다른 교과와 대학 작문 교과와의 관련성 등이 종합적으로 고찰되지 않으면 대학 작문 교육의 위상을 정립하거나 정체성을 찾는 일은 불가능해 보인다. 이 글에서 논의한 주요 내용은 다음과 같다. 첫째, 거시적 안목에서 (1) 대학의 기능과 대학 교육과정의 구성 방식, (2) 대학 교육과정에서 교양 교육의 위상, (3) 대학 교양 교육에서 작문 교육의 역할 등을 통해 대학 작문 교과의 정체성을 논의하고자 하였다. 둘째, 기초 조사와 선행 연구를 종합하여 대학 작문 교과 운영 방식과 문제점을 살피고자 하였다. 셋째, 대학 작문 교과 내적인 문제를 ‘목표’, ‘내용’, ‘교수ㆍ학습 방법’, ‘평가’의 차원에서 살피고 고등학교 교육과정과 연계성을 갖춘 표준 교육과정 설계의 필요성을 제기하고자 하였다. This study aims to review previous research on the college writing education. I think that the college education takes on historicity but the various advanced researches are interested in the need of actualities recently. But the identity of college writing education contains the complex problems. These problems involve three tasks. So I call these tasks as three preconditions. The college writing has been influenced by a total college curriculum. The college curriculum consists of specialty and general arts. The writing subjects belong to general arts. So I examined the college curriculum, general arts and college writing subjects. I discuss that the college writing has many-side aspects. Specially, I focus on the management system. The majority of the general arts or writing education system are not independent. And the purposes, contents, teaching-learning methods and assessment are not established. So I suggest the need of standard college writing curriculum. KCI Citation Count: 22